Polymerization initiation of pure 2-hydroxyethylmethacrylate under shock wave compression. (27th April 2022) - Jia, Zixian; Museur, Luc; Traore, Mamadou; Perruchot, Christian; Brajer, Jan; Bohm, Marek; Kanaev, Andrei
Abstract : The ability to initiate chemical reactions without the need for potentially hazardous solvents, catalysts and radical initiators is of key importance for modern biotechnologies and medicine. Abstract : The ability to initiate chemical reactions without the need for potentially hazardous solvents, catalysts and radical initiators is of key importance for modern biotechnologies and medicine. In this study, laser-driven shock wave compression was performed on pure 2-hydroxyethylmethacrylate (HEMA) free of any additives in order to trigger the polymerization process. We showed that the generated peak shock-wave pressure in the range between 2 and 5.5 GPa permitted initiation of radical polymerization and the formation of poly-HEMA oligomers. The reaction begins with diradicals HEMA2 ˙˙ appearing at the peak pressure and, by reactions with HEMA monomers, forming HEMA3 ˙˙ diradicals on the 15 ns timescale. The chain propagation further occurs on the sub-μs timescale by associations of the trimer diradicals, which, because of a smaller reactivity, do not react with HEMA monomers. The proposed method can be considered for scale-up of the polymerization process of ultrapure organics.